Analysing the causes of environmental management and audit scheme (EMAS) decrease in Europe. Issue 13 (10th November 2018) - Daddi, Tiberio; De Giacomo, Maria Rosa; Frey, Marco; Iraldo, Fabio
Abstract : Environmental Management and Audit Scheme( EMAS) is the most important public standard for an Environmental Management System. In the last few years, the number of certified organisations has been decreasing. Scholars have largely debated the drivers, barriers and benefits, but the recent decrease in EMAS registrations has not been sufficiently studied, leaving unsolved questions for scholars, practitioners and policy-makers. This paper aims to address this literature gap by (i) analysing the trends of other voluntary certification schemes in order to understand whether the decrease is a peculiarity of EMAS; (ii) investigating the reasons why formerly registered organisations have abandoned EMAS and why ISO14001 certified organisations do not adopt EMAS. The paper reports results of 17 interviews highlighting the lack of financial and human resources, the lack of market and stakeholder recognition, and the unclear added value of EMAS as reasons for the decrease of EMAS.